Features of formation of the individual students in secondary and high school - Sutula, V.O.; Sutula, A.V.; Golik, A.S.; Abdulvahid, D.N. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: Analyzed features of motivation to achievement and need to praise the students of secondary and high school. Material: In the survey took part 1634 students of secondary school in Kharkov, Vinnitsa and Lugansk regions. Carried out a comprehensive psychological testing, which allowed to find out the level of motivation of students to achievement and need for praise. Results: It is shown that during the period of study at school from fifth to eleventh classes a number of students have a low motivation to achievements, and low need for praise. Confirmed provision indicates that the modern school is still not fully realized the potential of educational pedagogy. Conclusions: It is shown that the formation personality physical education students in general education is possible only with the active and conscious of their participation in various forms of sports and recreation activities undertaken in the modern school.